2008
DOI: 10.21273/horttech.18.4.611
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Horticultural Responsibility on Health Indicators and Quality of Life in Assisted Living

Abstract: This study used quantitative and qualitative methods to investigate the impact of indoor gardening on elderly residents of a low-income assisted living facility over a 4-week period. Mastery, self-rated health, and self-rated happiness were pre-, post-, and post-post measured to evaluate whether a short-term introduction of indoor gardening that involved individual plant-care responsibility would improve these measures that are predictive of health and quality of life. Eighteen residents participated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…receiving social visits (Brown et al, 2004), were just as effective as active nature-based interventions, for psychological wellbeing. Other studies found improvements in apathy during exposure to a Virtual Reality forest (Moyle et al, 2018), and in happiness and mastery following a horticulture activity programme (Collins & O'Callaghan, 2008), but both were based on small samples and lacked control groups.…”
Section: Psychological Wellbeing Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…receiving social visits (Brown et al, 2004), were just as effective as active nature-based interventions, for psychological wellbeing. Other studies found improvements in apathy during exposure to a Virtual Reality forest (Moyle et al, 2018), and in happiness and mastery following a horticulture activity programme (Collins & O'Callaghan, 2008), but both were based on small samples and lacked control groups.…”
Section: Psychological Wellbeing Outcomesmentioning
confidence: 99%
“…Nine out of the ten active nature programmes involved interaction with real forms of nature through 'indoor gardening' (Brown, Allen, Dwozan, Mercer, & Warren, 2004;Lee & Kim, 2008;Powell, Felce, Jenkins, & Lunt, 1979;Tse, 2010); 'horticulture activities' (Barnicle & Midden, 2003;Collins & O'Callaghan, 2008;Masuya, Ota, & Mashida, 2014);or 'Horticulture Therapy' (D'Andrea et al, 2008;Yao & Chen, 2017) programmes. The distinction between these subtypes was unclear; all involved instructor-led activities related to cultivating plants, and most included group discussion.…”
Section: Active Nature Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Raske's study () was a qualitative one, but the sample consisted of a diverse group of residents, family members, staff and people in the community. The only study with which we can compare ours is that by Collins and O'Callaghan (). Our findings, from a different population group, echo their observations that engaging in indoor gardening brought happiness to older people in assisted living.…”
Section: Discussionmentioning
confidence: 99%
“…Horticultural therapy enhanced the quality of life of residents (Raske, 2010), improved their self-rated health and happiness (Collins & O'Callaghan, 2008) and significantly improved their life satisfaction and social networks (Tse, 2010). However, its use among older people who are frail and institutionalized remains under-studied and under-reported.…”
mentioning
confidence: 99%